Management and Infrastructure of Early Age Management Growing Early Childhood Education Inclusion in Growing Tegalrejo Yogyakarta - Najmah Sa’idah Fais Chanda, Rada (ACIECE, 2019)
This study aims to determine the application of facility and infrastructure management inGrowing PAUD inclusion in Tegalrejo Yogakarta. Researcher used qualitative descriptive reseach with the subject of the study was the Principal Drowing PAUD inclusion Tegalrejo Yogyakarta. Data collection uses the structured interview method and is used using interactive data analysis techniques, using four stages in analyzing, which starts with data collection, data presentation and drawing conclusions. According to PERMENDIKBUD NO.137 IN 2014 that the result of the study showed that the facilities and infrastructure of Growing PAUD inclusion in Tegalrejo Yogyakarta werw adequate. Infrastructure faciliies in Growing PAUD inclusion in Tegalrejo Yogyakarta include: indor facilities and infrastructure such as cars. Cooking utensils, beams, legos, mazes, ac etc. For failities and outdoor infrastructure consist of: Slides, swings, globe, seesaw, ball bath etc. Besides the facilities and infrastructure in Growing PAUD inclusion in Tegalrejo Yogyakarta, there are leadership chairs, shelves made by students, guest chairs, role play trash bins, cupboards, longterm drawings, wall clocks, wash basins, wall clocks etc